Fix-Up Strategy on Students’ Narrative Text Reading Achievement at SMP Negeri 19 Palembang - Sahri Sahri (CV. ULIL ALBAB CORP, 2025)
EFL students in Indonesia are reluctanr readers. This is evidenced in the PISA results in 2018 to 2022 which show that Indonesian students have low reading skills. Therefore, the purpose of this study was to investigate the use of Fix-Up Startegy to improve students’ reading achievement in narrative text in grade seven of SMP Negeri 19 Palembang, and the experimental class students’ perception towards the use of Fix-Up Strategy. In this research design used in the study was a quasi-experimental design. The samples of this study were VII.3 and VII.5 classes consisting of 34 students for each class. Data were collected to give pre-test and post-test, and analysed using t-test (paired sample t-test and independent sample t-test) with the help of SPSS v.27. This study shows that the p-value of paired samples is 0.000 which is less than 0.05, as well as the p-value of each reading in the experimental group is less than 0.05, and it means that there is a significant increase in students' reading achievement after being taught by using Fix-Up Strategy. Furthermore, the p-value of the independent sample t-test is 0.000 which is less than 0.05, which means that there is a significant difference between the experimental group and the control group, and the experimental class students showed a positive response and perception towards learning in students' reading achievement by using the Fix-Up Strategy. Therefore, the result of this study shows that the use of fix-up strategy can improve students’ reading achievement in narrative text in grade seven of SMP Negeri 19 Palembang.